Capital Estimation: Theory and US-Japan Comparative Study - Eric Iksoon Im; Tam Bang Vu (Journal of Basic & Applied Sciences, 2013)
Capital stock estimation is a thorny task to deal with. To circumvent the problem, we derive a function which does not contain capital stock, yet whose regression indirectly estimates the production function. Consequently, the estimated production function can generate the capital stocks and depreciation rates. The approach applied to US data resulted in estimates of both production function and capital stock very close to those differently estimated in existing literature. Japan data are then applied as a comparative study.